The determinants of capital structure: an empirical study of Omani listed industrial companies - Al Ani, Mawih; Al Amri, Maha (Business: Theory and Practice, 2015)
This study investigates five determinants of capital structure (leverage) in three subsectors of the Omani Industrial companies (food, construction and chemical) listed on Muscat Securities Market for the period 2008–2012. According to available information and literature review, the determinants are profitability measured by return on assets (ROA), risk measured by the standard deviation of return on assets, the size of the company measured by the natural logarithm of total assets, rate of growth measured by the market-book value ratio (P/E) and assets tangibility measured by fixed assets to total assets ratio. The capital structure or leverage is measured by total debt ratio. In the industrial sector as whole; the findings of the study indicate that there is a statistically positive association between risk and tangibility and leverage. Also, there is a statistically negative association between growth rate and profitability and leverage, while there is no association with size. Regression analysis indicates that size, tangibility and risk have a statistically significant effect on leverage.